The subliminal interactions of the dimensions of employee engagement with employee performance - Ravhudzulo, Hangwani Raymond; Eresia-Eke, Chukuakadibia (Frontiers in Organizational Psychology, 2025)
The Coronavirus pandemic has significantly altered work environments, necessitating high levels of employee engagement and adaptability to keep up with technological advancements and market demands. This study focuses on understanding how different engagement dimensions (physical, cognitive, emotional) influence employee performance dimensions (task, adaptive, contextual) within the South African Information Communication Technology sector. Using a quantitative methodology and Partial Least Squares Structural Equation Modeling, the study analyzed 478 responses from employees in the Information Communication Technology sector of South Africa, collected through an online survey. Findings indicate a statistically significant positive relationship between physical engagement and employee performance, and similarly between cognitive engagement and performance. Conversely, the relationship between emotional engagement and performance was found to be statistically insignificant. These findings suggest that managers should encourage physical activity, for example, by creating ergonomic workplaces for their employees, which can contribute to improved work performance. The generalizability of the findings is constrained through the utilization of a non-probability sampling technique. Nonetheless, this study contributes novel and empirical data and insights to the understanding of the multifaced nature of employee engagement and its relationship with employee performance, distinguishing the roles of physical, cognitive, and emotional engagement in the South African Information Communication Technology sector. It challenges existing models, provides data from a developing context, and offers practical managerial actions. This study pioneers the exploration of distinct employee engagement dimensions and how they relate with performance, advancing employee engagement literature, and offering a new perspective by conceptualizing employee performance as a unidimensional construct in the South African Information Communication Technology sector.